Orthostatic hypotension in internal medicine wards. (3rd June 2019) - Tzur, Irma; Izhakian, Shimon; Gorelik, Oleg
Abstract: Objectives: Most studies of orthostatic hypotension (OH) have focused on community-dwelling and institutionalized patient populations. Less is known about OH in hospitalized patients. Moreover, a comprehensive review of OH in internal medicine wards has not been published in the English literature. Our purpose is to provide current information regarding OH in internal medicine inpatients. Methods: A comprehensive search of medical databases was performed for potentially relevant articles, using the following keywords: postural or orthostatic hypotension, with the combination of hospitalization or internal medicine. Inclusion criteria were: population of patients hospitalized for acute disorders in internal medicine or geriatric wards with a sample size of ≥50 and publication as an original full-length article in the English language. Data from 14 selected studies are reviewed, including: pathophysiology, evaluation, prevalence, manifestations, risk factors, prognosis, and management. Results: OH is a common and often symptomatic disorder in elderly internal medicine patients. The prevalence of OH in this population ranges from 22–75%. There are substantial discrepancies between the studies reviewed regarding definitions and means of evaluating OH. OH in internal medicine wards is largely non-neurogenic and multifactorial. The main predisposing factors for OH are prolonged bed rest, hypertension, and heart failure. OH in internal medicine wards is managed mainly with non-pharmacologic interventions, and is frequently reversible. Conclusions: In internal medicine inpatients, OH warrants attention because this disorder is common, potentially dangerous, and treatable. In the hospital setting, OH should be routinely assessed on ambulation, following the current guidelines for OH definition and meaning.